2020
DOI: 10.1017/s0031182020001535
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between CE cyst characteristics and genetic diversity of Echinococcus granulosus sensu lato in humans from Turkey

Abstract: Cystic echinococcosis (CE) is one of the most common zoonotic diseases worldwide, particularly in rural areas. This study aimed at the identification of the genotype/species belonging to Echinococcus granulosus sensu lato (s.l.) specimens in retrieved percutaneously from the human host and to investigate their relationship with cyst characteristics. The genetic identification of cyst material was performed by mt-CO1 gene polymerase chain reaction, and confirmed via sequencing. A total of 110 CE cysts were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…These host-adapted genotypes of E. granulosus s.l. have demonstrated varied pathogenicity and organ affinity in humans (Alvarez Rojas et al, 2014;Örsten et al, 2020;Sadjjadi et al, 2013), geographical distribution (Deplazes et al, 2017;Ito et al, 2017), host preference (Ohiolei et al, 2020), transmission dynamics (Carmena & Cardona, 2014;Cerda et al, 2018), adult worm morphology (Lymbery et al, 2015) and genome (Maldonado et al, 2017(Maldonado et al, , 2019Zheng et al, 2013). For instance, based on two systematic reviews, camels and pigs act as important intermediate hosts for G6 and G7, respectively (Anvari et al, 2021a;Cucher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These host-adapted genotypes of E. granulosus s.l. have demonstrated varied pathogenicity and organ affinity in humans (Alvarez Rojas et al, 2014;Örsten et al, 2020;Sadjjadi et al, 2013), geographical distribution (Deplazes et al, 2017;Ito et al, 2017), host preference (Ohiolei et al, 2020), transmission dynamics (Carmena & Cardona, 2014;Cerda et al, 2018), adult worm morphology (Lymbery et al, 2015) and genome (Maldonado et al, 2017(Maldonado et al, , 2019Zheng et al, 2013). For instance, based on two systematic reviews, camels and pigs act as important intermediate hosts for G6 and G7, respectively (Anvari et al, 2021a;Cucher et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, based on two systematic reviews, camels and pigs act as important intermediate hosts for G6 and G7, respectively (Anvari et al., 2021a; Cucher et al., 2016). Updated epidemiological data of human CE suggested that compared to G1 mainly in the liver infection, G6 and G7 showed a more diverse distribution of infected organs, such as brain or spleen (Cucher et al., 2016; Örsten et al., 2020; Sadjjadi et al., 2013). The Belt and Road Network for the Elimination and Control of Echinococcosis and Cysticercosis was established in 2017 (Qian & Zhou, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, all the isolates collected in this study were confirmed by BLAST algorithm as E. granulosus s.l. From Turkey, there are several reports on molecular characterization of E. granulosus s.l isolates from various intermediate hosts (Schneider et al 2008;Utuk et al 2008;Snabel et al 2009;Ergin et al 2010;Simsek et al 2011;Utuk and Simsek 2013;Bakal et al 2015;Eroglu et al 2016;Orsten et al 2018;Kurt et al 2020;Örsten et al 2020). These studies showed that E. granulosus s.s. (genotypes G1-G3) is the predominant species obtained from hydatid materials in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…104 of 110 isolates were identified as E. granulosus s.s. (G1-G3) and six isolates of 110 were identified as E. canadensis (G6/7). [27] In the study from Van province, 102 echinococcal cysts were collected from the operated patients and the genomic analysis was performed using ITS1 fragment by PCR-RFLP and mt-CO1 gene by PCR and after evaluate with sequencing. Consequently, all isolates was found to be accordence with G1-G3 genotypes.…”
Section: Human-based Studiesmentioning
confidence: 99%